Expression of Fas (CD95) and Fas ligand on peripheral blood mononuclear cells in critical illness and association with multiorgan dysfunction severity and survival - Papathanassoglou, Elizabeth; Moynihan, Jan; McDermott, Michael (My University, 2001)
Objective: This was an exploratory study with three goals: a) to quantify the expression of the apoptotic receptor Fas and its ligand (FasL) on peripheral blood mononuclear cells (PBMCs) in patients with, or at risk for, multiple organ dysfunction syndrome (MODS); b) to compare this expression with the respective expression in matched controls; and c) to explore the association with MODS severity and survival. Design: Repeated-measures correlational and cross-sectional design. Setting: The surgical, medical, and the trauma/burn intensive care unit of an academic institution. Patients: Thirty-five adult, critically ill patients meeting the diagnostic criteria for systemic inflammatory response syndrome (SIRS) with MODS, or at risk for MODS, were followed for 14 days. Thirty-five non-SIRS controls matched with patients for age, gender, and race comprised the control group. Interventions: Peripheral blood sampling every 48 hrs. Measurements/Main Results: T cells were considerably depleted in SIRS/MODS patients (p < .001), and Fas and FasL expression on PBMCs (flow cytometric analysis) was elevated significantly compared with controls (p < .001). In contrast to controls, non-T cells were the major sources of Fas and FasL in SIRS/MODS patients (p < .01). Expression of Fas and FasL exhibited a bimodal correlation with severity (p < .03). High severity patients demonstrated increasing Fas and FasL expression with increasing severity in contrast to declining expression in moderately severe patients. Fas and FasL measurements were significantly and positively associated with the likelihood of survival (p < .05). Conclusions: Dysregulation in the expression of apoptotic receptors Fas and FasL, at least in PBMCs, may be involved in the pathophysiology of SIRS, the related lymphocytopenia, and the onset of MODS and the related morbidity and mortality rates
Keywords: Critical care medicine; Catastrophic illness; Apoptosis; Cytokines; Multiple organ failure; Nitric oxide; T cells; Tumor necrosis factor; Cell death